Soybean Production: Planting Date × Variety, Southeast Kansas - G. F. Sassenrath; I. A. Ciampitti; D. E. Shoup (Kansas Agricultural Experiment Station Research Reports, 2015)
Optimal soybean planting in southeast Kansas usually occurs from mid-May to mid- June for full-season or late June to early July for double-cropped soybean. Planting is timed to capture fall rains and cooler temperatures during critical periods of bean development and yield formation to avoid midsummer heat and drought.
Keywords: soybean; planting date; southeast Kansas